Taḥlîl ad-Dalâly ‘an ar-Rûḥ fi at-Tafsîr - Rochmad; Ghulam Hilman (Studia Quranika, 2018)
This study uses a semantic approach, which tries to explain the meaning of rûh in the Qur'an. Term rûh has a variety of meanings and views from various points of view. Such as from the view of sufi, it will be different from the meaning of rûh that exists in the Qur'an. Further more, in semantics has two ways in the approach of meaning, namely the basic meaning and relational meaning. The basic meaning of term rûh that exists in the Qur'an has 8 meanings, namely grace, angel, gabriel, isa, life, revelation, wind, and comfort. While the basic meaning is spirit of rûh, wind, and comfortable. When all these meanings are meant to be understood, it could be conclude that rûh is something ghoib, lively, holy and clean of all disrepute, makes man live, so that he can do a kindness